Design of Incu Analyzer for IoT-based Baby Incubator Calibration - Septiana, Silvi Dwi; Syaifudin, Syaifudin; Maghfiroh, Anita Miftahul; Huynh, Phuoc-Hai (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Incubator Analyzer is a calibration tool that measures baby incubators' temperature, mattress temperature, humidity, airflow, and sound level. This research aims to design an